2014
DOI: 10.1021/np5006554
|View full text |Cite
|
Sign up to set email alerts
|

Antitrypanosomal Quinoline Alkaloids from the Roots of Waltheria indica

Abstract: Chemical investigation of the dichloromethane root extract of Waltheria indica led to the isolation and characterization of 10 quinoline alkaloids, namely, 8-deoxoantidesmone (1), waltheriones E-L (2-9), and antidesmone (10). Among these, compounds 2-9 have not yet been described in the literature. Their chemical structures were established by means of spectroscopic data interpretation including (1)H and (13)C NMR, HSQC, HMBC, COSY, and NOESY experiments and UV, IR, and HRESIMS. The absolute configurations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
88
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 20 publications
2
88
0
1
Order By: Relevance
“…[99][100][101][102][103] The dichloromethane root extract showed activities against T. cruzi (IC50 = 0.74 μg/mL), T. b. brucei (2.3% survival at 20 μg/mL) and T. b. rhodesiense (IC50 = 17.4 μg/mL). 98 With the exception of waltherione L (26), with a slightly higher IC50 (3.1 μM), the isolated compounds all displayed potent growth inhibition toward the amastigote form of T. cruzi (the Tulahuen C4 strain), with IC50 values lower than that of the reference drug benznidazole (IC50 = 2.9 μM). Structureactivity relationships (SARs) provide suggestions that, a methoxy group, bound to the nitrogen atom is important for activity (e.g.…”
Section: Quinolinesmentioning
confidence: 94%
See 1 more Smart Citation
“…[99][100][101][102][103] The dichloromethane root extract showed activities against T. cruzi (IC50 = 0.74 μg/mL), T. b. brucei (2.3% survival at 20 μg/mL) and T. b. rhodesiense (IC50 = 17.4 μg/mL). 98 With the exception of waltherione L (26), with a slightly higher IC50 (3.1 μM), the isolated compounds all displayed potent growth inhibition toward the amastigote form of T. cruzi (the Tulahuen C4 strain), with IC50 values lower than that of the reference drug benznidazole (IC50 = 2.9 μM). Structureactivity relationships (SARs) provide suggestions that, a methoxy group, bound to the nitrogen atom is important for activity (e.g.…”
Section: Quinolinesmentioning
confidence: 94%
“…98 This plant is used in traditional medicine for the treatment of several ailments, including malaria. [99][100][101][102][103] The dichloromethane root extract showed activities against T. cruzi (IC50 = 0.74 μg/mL), T. b. brucei (2.3% survival at 20 μg/mL) and T. b. rhodesiense (IC50 = 17.4 μg/mL).…”
Section: Quinolinesmentioning
confidence: 99%
“…lobata, and A. archangelica) were selected. The extracts were prepared in order to insure that they contain the metabolites that are ingested when the medicinal plant is orally taken: a methanolic extract of the fruits from A. archangelica mostly composed of furanocoumarins [43,44], a decoction of aerial parts of W. indica containing quinoline alkaloids [33], and a decoction of roots of P. montana var. lobata with flavonoid glycosides [35].…”
mentioning
confidence: 99%
“…A complementary LC-MS-based dereplication indicated that the more lipophilic NPs belong to the quinoline alkaloids waltherione C, E, and G and to flavonoid aglycones, whereas the more polar group of constituents included cyclopeptide alkaloids adouetin X and Y [33,34]. The effective passive permeability values of the pharmacologically active waltheriones C, E, and G were calculated and such compounds were found to have medium permeability (l " Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation